Identification of Physical and Spiritual Activities Among Patients with Hypertension in Maintaining Health Status - Sri Rahayu; Shelin Putri Malvasari; Vany Septa Viani (Utan Kayu Publishing, 2022)
Online activities during the pandemic have changed people's lifestyles, including patients with chronic diseases. Without realizing it, patients with hypertension are less mobile, tend to sit, rarely exercise, rarely control their health, and eventually lead to sedentary behavior. This sedentary behavior risks the emergence of other health problems. Hence, it is necessary to identify the physical and spiritual activities of patients with hypertension to maintain and improve their health status. For this reason, this study aims to identify the physical and spiritual activities of patients with hypertension in maintaining their health status. The research used a quantitative method with a cross-sectional study design. Respondents involved in this study were 84 patients with hypertension with limited inclusion and exclusion criteria. The results showed that most patients with hypertension were 37 adults (44.0%), 52 people (61.9%) were female, 56 people (66.7%) had senior high school education, 36 people (42.9%) were housewives, 45 people (53.6%) had low activity, 100% active in spiritual activities, and having health status, i.e., sometimes sick, were 40 people (47.6%). Suggestions for further research are to identify differences in physical activity and health status in other chronic diseases, such as patients with Diabetes Mellitus.